The Role of Task Force SUP IVA (Task Force Husband Peduli IVA) on IVA Examination Behavior in WUS - Ratnawati, Yunni; Chunaeni, Siti; Rofi'ah, Siti (Midwifery and Nursing Research, 2024)
Background : The total number of women aged 30-50 years in Temanggung Regency who underwent IVA (Visual Acetic Acid Inspection) examination for early diagnosis of cervical cancer was reported to be 2,127, which accounts for 1.1% of the total population of 114,035 women in that age group. The proportion of WUS who conduct VIA examinations is still well below the established aim of 10% (Dinkes Temanggung, 2022). This study seeks to ascertain the impact of the IVA SUP Task Force (IVA Concerned Husband Task Force) on the conduct of IVA examinations in WUS.Methods : This type of research uses quasi-experiments with design only with control group design. The population in this study was all men who had wives aged 30-50 years in Coyo, Dayohan, and Jekaton Hamlets of Wonosari Village who had not done IVA examination totaling 197 people. The sample amounted to 130 respondents into the intervention group and 30 respondents into the control group. The sampling technique uses purposive sampling. The statistical test of this study used the Chi Square test.Result : The group that received counseling from the SUP IVA Task Force (Task Force Husband Peduli IVA), as many as 11 people (16.9%) carried out IVA examinations. The group that received counseling for female IVA cadres, as many as 6 people (9.2%) carried out IVA examinations. There was no difference in IVA examination behavior in the group that received counseling from the SUP IVA Task Force (Task Force Husband Peduli IVA) with the group that received counseling for female IVA cadres (p value = 0.298). Conclusion: there is no influence on the role of Task Force SUP IVA (Task Force Husband Peduli IVA) on IVA examination behavior. Conclusions : Provide input to health workers to involve the role of the husband in the behavior of IVA examination in WUS. Keywords : Task Force on the role of husbands, cadres, WUS, IVA